Bibliometric Analysis Using Publish or Perish and VOSviewer :Machine Learning in Relation to Cardiovascular Disease - Akbar Sidqi (Jurnal Informatika dan Sains Media (JISMA), 2024)
Cardiovascular disease, commonly known as heart disease, is a condition where blood vessels narrow or become blocked, potentially leading to heart attacks, angina, or strokes. Disorders affecting the heart muscle, valves, or rhythm are also considered forms of heart disease. According to the American Heart Association (2017), Cardiovascular disease causes approximately 17.3 million deaths worldwide, with around 3 million of these occurring before the age of 60. Global statistics indicate that there are 9.4 million deaths annually due to cardiovascular disease, of which 45% are attributed to coronary heart disease. It is estimated that this number will increase to 23.3. million in 2030. This research is to identify patterns and trends and comprehensively evaluate data on cardiovascular disease. The method used is bibliometric analysis and VosViewer with a minimum number of term occurrences of 3 clusters with 96 relevant terms to visualize entity relationships, patterns and trends. In the analysis process, 50 articles were used to obtain scientific publications related to the topic of cardiovascular disease from the 2020-2024 period. with VosViewer you can produce the latest gaps and data analysis.